2006
DOI: 10.4049/jimmunol.176.11.6935
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HLA-A*0201-Presented T Cell Epitopes Derived from the Oncofetal Antigen-Immature Laminin Receptor Protein in Patients with Hematological Malignancies

Abstract: The oncofetal Ag immature laminin receptor (OFA-iLR) is a potential target molecule for immunotherapeutic studies in several tumor entities, including hematological malignancies. In the present study, we characterize two HLA-A*0201-presented epitopes eliciting strong OFA-iLR peptide-specific human cytotoxic T cell (CTLs) responses in vitro. Both allogeneic HLA-A*0201-matched and autologous CTLs recognized and killed endogenously OFA-iLR-expressing tumor cell lines and primary malignant cells from patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…25 CD8 þ T cells specific for G250/CAIX [24][25][26][27][28][29][30][31][32] , G250/CAIX 254-262 and RHAMM [165][166][167][168][169][170][171][172][173] are also regularly detected in the peripheral blood of AML patients, with frequencies of 60%, 13% and 47%, respectively. 25 In a series of 15 AML patients, Siegel et al 22 observed spontaneous T-cell immune responses to different HLA-A*0201-restricted T-cell epitopes derived from OFA-iLRP, including iLR1 [59][60][61][62][63][64][65][66][67][68] (6/15) …”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
See 1 more Smart Citation
“…25 CD8 þ T cells specific for G250/CAIX [24][25][26][27][28][29][30][31][32] , G250/CAIX 254-262 and RHAMM [165][166][167][168][169][170][171][172][173] are also regularly detected in the peripheral blood of AML patients, with frequencies of 60%, 13% and 47%, respectively. 25 In a series of 15 AML patients, Siegel et al 22 observed spontaneous T-cell immune responses to different HLA-A*0201-restricted T-cell epitopes derived from OFA-iLRP, including iLR1 [59][60][61][62][63][64][65][66][67][68] (6/15) …”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
“…Their expression is repressed in normal adult tissues, making it unlikely that oncofetal antigen-targeted immunotherapy elicits autoimmunity. 21,22 ETO, also known as MTG8, which is found to be overexpressed in leukemic cells carrying the t(8;21) chromosomal translocation, 23 is another example of a relatively tumor-specific LAA. Physiological expression of MTG8 appears to be predominantly restricted to the human brain and heart.…”
Section: Introductionmentioning
confidence: 99%
“…However, immunization with iLRP in a mode that only or at least primarily induces Th1 and cytotoxic CD8 T cells could be used in cancer immunotherapy. One such mode would be by immunizing with autologous dendritic cells pulsed with iLRP or iLRP peptides that induce Th1 and cytotoxic T cells, but not with IL-10-secreting CD8 T cells [47,49]. The in vivo antitumor efficacy of iLRP was also demonstrated by immunization of BALB/c mice with recombinant iLRP entrapped in liposomes and challenge with a tumorigenic dose of murine fibrosarcoma MCA1315 cells [50].…”
Section: Autoimmunogenicity Of 37-kda Ofa/ilrp To Pregnant Mothersmentioning
confidence: 99%
“…iLRP is important to the tumor cells for invasion and metastasis [26], and most metastatic human tumors express increased amounts of this protein [43]. While early studies were confined to rodent tumor and pregnancy models, recent work has been focused on human malignancies, such as head and neck cancer [44], breast cancer [31], renal cancer [32,45], hematological malignancies [33,[46][47][48], and several other types of cancer [34].…”
Section: Autoimmunogenicity Of 37-kda Ofa/ilrp To Pregnant Mothersmentioning
confidence: 99%
“…6,7 In contrast, OFA/iLR is re-expressed on a broad range of malignancies including some hematological tumor entities. [8][9][10] By utilizing a mouse anti-OFA/iLR monoclonal antibody (Dr J Coggin, Mobile, Al, USA) we show that OFA/iLR is frequently expressed on the surface of malignant plasma cells of patients with MGUS, MM and plasma cell leukemia (Figures 1a and b). For immunohistochemical staining Letters to the Editor and flow cytometry analysis goat anti-mouse immunoglobulin as a secondary antibody coupled to alkaline phosphatase (panel a) or to FITC (panels b and c) was used.…”
mentioning
confidence: 99%